Environmental factors controlling zooplankton communities in thermokarst lakes of the Bolshezemelskaya Tundra permafrost peatlands (NE Europe) - Sobko, Elena I.; Shirokova, Liudmila S.; Klimov, Sergey I.; Chupakov, Artem V.; Zabelina, Svetlana A.; Shorina, Natalia V.; Moreva, Olga Y.; Chupakova, Anna A.; Vorobyova, Taissia Ya (Water)
Environmental physical and chemical factors controlling the abundance and biodiversity of zooplankton in permafrost‐affected lakes are poorly known yet they determine the response of aquatic ecosystems to on‐going climate change and water warming. Here, we assess the current status of zooplankton communities in lakes of the Bolshezemelskaya Tundra (permafrost peatlands of NE Europe), and provide new information about the composition and structure of zooplankton. The results demonstrate that the structure of zooplankton communities is influenced by the mor‐ phometric features of lakes and the degree of lake overgrowth by macrophytes. According to the level of quantitative development of zooplankton, most tundra lakes were of the oligotrophic type with an average wet biomass of up to 1 g/m3. The largest number of species was observed in zoo‐ plankton communities of small thaw ponds with an area of up to 0.02 km2 and overgrown with macrophytes. The analysis of factors that influence the formation of the lake zoocenosis demon‐ strated that the species composition and quantitative characteristics of zooplankton are chiefly con‐ trolled by pH and water mineralization. A comparison of the results obtained with the literature data on the lakes of this region collected 60 years ago suggests that the ecosystems of these lakes are in a stable state. Overall, these new insights will improve our knowledge of factors controlling the zooplankton spatial dynamics in unique but quite abundant thermokarst lakes of NE European Tundra, subjected to on‐going climate warming.